2011
DOI: 10.1111/j.1753-5174.2011.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study to Assess the Safety, Tolerability and Pharmacokinetics of AZD4877 in Japanese Patients with Solid Tumors

Abstract: IntroductionAZD4877 is a potent Eg5 inhibitor that has been shown to have an acceptable tolerability profile in a Phase I study of Western patients with solid tumors. This study was conducted to evaluate the safety, pharmacokinetic (PK) profile, maximum tolerated dose (MTD) and efficacy of AZD4877 in a Japanese population with solid tumors.MethodsIn this Phase I, open-label, dose-escalation study, AZD4877 (10, 15, 20 or 25 mg) was administered as a 1-hour intravenous infusion on days 1, 8 and 15 of repeated 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Ispinesib (also named SB-715992 or CK0238273) is a potent and selective inhibitor of Eg5 that is currently in multiple phase II clinical trials (Burris et al, 2011;Souid et al, 2010) and is one of the most advanced drug candidates. The importance of the quinazolin-4-one scaffold targeting Eg5 is further underlined by the fact that three structurally related compounds are in various stages of clinical development: SB-743921, a second-generation ispinesib analogue (Holen et al, 2011), AZD4877 (Esaki et al, 2011) and Arq621 (Chen et al, 2011). A greater understanding of the molecular details of the protein-inhibitor interactions of this class of compounds is therefore crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Ispinesib (also named SB-715992 or CK0238273) is a potent and selective inhibitor of Eg5 that is currently in multiple phase II clinical trials (Burris et al, 2011;Souid et al, 2010) and is one of the most advanced drug candidates. The importance of the quinazolin-4-one scaffold targeting Eg5 is further underlined by the fact that three structurally related compounds are in various stages of clinical development: SB-743921, a second-generation ispinesib analogue (Holen et al, 2011), AZD4877 (Esaki et al, 2011) and Arq621 (Chen et al, 2011). A greater understanding of the molecular details of the protein-inhibitor interactions of this class of compounds is therefore crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the results were disappointing. In the phase I trials in solid tumor patients (NCT00613652 and NCT00389389), neutropenia was the most common DLT [ 217 , 218 ]. No objective responses were observed, with 31% and 27% of patients achieving SD, respectively [ 217 , 218 ].…”
Section: Eg-5 Kinesinmentioning
confidence: 99%
“…In the phase I trials in solid tumor patients (NCT00613652 and NCT00389389), neutropenia was the most common DLT [ 217 , 218 ]. No objective responses were observed, with 31% and 27% of patients achieving SD, respectively [ 217 , 218 ]. Other trials with AML (NCT00486265) and urothelial cancer (NCT00661609) patients demonstrated similar efficacy.…”
Section: Eg-5 Kinesinmentioning
confidence: 99%
“…SB743921, a derivative of ispinesib and found to be 5-fold more potent against ATPase activity of Eg5, is undergoing phase II clinical trials . AZD4877, MK0731, ARQ621, and ARRY520 have progressed to various stages of clinical development.…”
mentioning
confidence: 99%